Periprocedural Myocardial Injury during Percutaneous Coronary Intervention: How can it be prevented? - Kabir, CM Shaheen; Haq, M Maksumul; Rashid, MA; Taimur, Syed Dawood Md; Rahman, Md Hasanur; Gomes, Hemanta I; Salahuddin, Md; Jahan, Mah-Noor (Ibrahim Cardiac Medical Journal, 2013)
DOI: http://dx.doi.org/10.3329/icmj.v2i1.17418 Ibrahim Cardiac Med J 2012; 2(1): 51-56